Luiz Gama, um intelectual diaspórico: intelectualidade, relações étnico-raciais e produção cultural na modernidade paulistana (1830-1882) - Santos, Eduardo Antonio Estevam (2014)
This academic paper interprets and analyzes the trajectory and cultural production of the poet, journalist, mason, abolitionist, lawyer ("rábula") and political leader Luiz Gama. The city of São Paulo was the space for his accomplishments, quintessential place for the emergence of his political and diasporic identity, to his legal struggles on behalf of enslaved and the stage for the emergence of liberal-republican positions wich, to Gama, Gama, were inseparable from slave liberation. We prioritize, in the analysis of their narratives, how Luiz Gama used race, identity, modernity and memory of slavery to mediate the social reality of São Paulo and ethno-racial relations. Under the analytical perspective of cultural studies and postcolonial criticism, we seek to find Luiz Gama in frames of an intellectuality formed beyond the national space